A porous titanium alloy implant double-layer sustained-release system and its preparation method and application

By constructing a double-layer hydrogel system in porous titanium alloy implants, the inner layer is loaded with bone functional substances and the outer layer is loaded with anti-tumor drugs, which solves the problem of lack of temporal and spatial order of anti-tumor and bone substance release in the prior art, achieves the sustained release of drugs and promotes bone cells, and improves the therapeutic effect.

CN119367594BActive Publication Date: 2025-04-08SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411962591.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing porous titanium alloy implants lack space-time sequence in the release of anti-tumor and bone-promoting substances, and the penetration and durability of the anti-tumor drug doxorubicin are insufficient.

Method used

A double-layer hydrogel system is adopted, in which the inner gel contains DNA-like nanotubes and hydroxyapatite, and the outer gel contains DNA-like nanotubes loaded with anti-tumor drugs. Through this structure, the drug is sustained release and bone cells are promoted.

Benefits of technology

The release of anti-tumor and bone substances is achieved in a time-space order, which improves the penetration and durability of doxorubicin to tumors, and promotes the repair and regeneration of bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367594B_ABST
    Figure CN119367594B_ABST
Patent Text Reader

Abstract

The present invention proposes a porous titanium alloy implant double-layer sustained-release system and its preparation method and application, which belong to the biological field. The porous titanium alloy implant double-layer sustained-release system provided by the present invention uses a porous titanium alloy as a skeleton, the porous titanium alloy is loaded with a first gel inside, and the porous titanium alloy is coated with a second gel outside; the first gel contains DNA-like nanotubes and hydroxyapatite; the second gel contains DNA-like nanotubes loaded with anti-tumor drugs, and the physical and chemical properties and degradation rates of the inner and outer gels are different, which not only solves the problem of the current porous titanium alloy implant simultaneously releasing anti-tumor and osteogenic substances, but also lacks the problem of time and space order; it also increases the retention of tumors, providing a solution to the poor retention of anti-tumor drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, and in particular relates to a porous titanium alloy implant double-layer sustained-release system and a preparation method and application thereof. Background Art

[0002] The statements in this section merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Bone defects caused by bone tumor surgery need to be filled with implants, and porous titanium alloy implants have been used in the medical field. Usually, in order to give implants anti-tumor and osteogenic capabilities, it is necessary to use mechanical, physical or chemical methods to modify the surface of the implant or inject drugs into the porous titanium alloy implant through hydrogel. However, the implants obtained in this way release anti-tumor and osteogenic substances at the same time, lacking a temporal and spatial order, and cannot meet clinical needs.

[0004] Hydroxyapatite is the main inorganic component of human bone. Current research focuses on loading it on the surface of implants through surface modification. However, there is a problem of uneven surface modification in porous implants. In addition, the lack of collagen, an important organic component in human bone, makes it impossible to provide anchoring points for cells and form the initial framework of bones during the differentiation of mesenchymal stem cells into osteoblasts, which is also a difficult problem to solve at present.

[0005] Doxorubicin is a broad-spectrum anti-tumor hydrophobic drug commonly used in clinical practice. It is currently mostly delivered via hydrogels, but there are still problems such as difficulty in drug loading, fast release rate, and poor retention of released drug molecules in tumor spheres.

[0006] Therefore, it is of great significance to develop implants that release antitumor and osteogenic substances in a spatiotemporal order. Summary of the invention

[0007] In order to overcome the above-mentioned deficiencies of the prior art, one of the purposes of the present invention is to solve the problem of the current porous titanium alloy implant releasing anti-tumor and osteogenic substances simultaneously and lacking spatiotemporal order by constructing a double-layer hydrogel system with different internal and external physicochemical properties and degradation rates;

[0008] The second purpose of the present invention is to solve the problem that the anti-tumor drug doxorubicin has poor penetration into tumors and poor durability of its effect.

[0009] To achieve the above objectives, one or more embodiments of the present invention provide the following technical solutions:

[0010] In a first aspect of the present invention, a porous titanium alloy implant double-layer sustained-release system is provided, wherein the porous titanium alloy implant double-layer sustained-release system uses a porous titanium alloy as a skeleton, a first gel is loaded inside the porous titanium alloy, and a second gel is coated outside the porous titanium alloy;

[0011] The first gel contains DNA-like nanotubes and hydroxyapatite;

[0012] The second gel contains DNA-like nanotubes loaded with anti-tumor drugs.

[0013] In some embodiments of the present invention, the anti-tumor drug includes doxorubicin.

[0014] In some embodiments of the present invention, the first gel is agarose gel, and the second gel is sodium alginate and gelatin gel. Gelatin is a thermosensitive hydrogel, and the present invention uses gelatin to control drug sustained release and accelerate drug release at 37°C.

[0015] The porous titanium alloy implant double-layer sustained-release system provided by the present invention has both the functions of promoting bone formation and resisting tumors, and can be used to treat bone tumors.

[0016] The present invention finds that the double-layer sustained-release system of the porous titanium alloy implant internally loaded with gel promoting bone formation and DNA-like bionic nanotubes can effectively increase the penetration of tumor drugs into tumors and the durability of their effects.

[0017] The second aspect of the present invention provides a method for preparing the porous titanium alloy implant double-layer sustained-release system according to the first aspect, comprising:

[0018] The porous titanium alloy implant was subjected to flow acid etching;

[0019] The DNA-like nanotubes and hydroxyapatite are mixed and added into an agarose solution to obtain a first mixed solution;

[0020] injecting the first mixed solution into the porous titanium alloy implant after flow acid etching, and then immersing the porous titanium alloy implant in a calcium salt solution;

[0021] The DNA-like nanotubes and the anti-tumor drug are mixed and added into a sodium alginate and gelatin solution to obtain a second mixed solution;

[0022] The porous titanium alloy implant immersed in the calcium salt solution is taken out and then placed in a second mixed solution, left to stand, and then taken out to obtain a porous titanium alloy implant double-layer sustained-release system.

[0023] In some embodiments of the present invention, the concentration of the agarose solution is 0.01-0.02 g / mL, and the solvent is PBS.

[0024] In some embodiments of the present invention, in the first mixed solution, the concentration of DNA-like nanotubes is 1.5-2 μg / mL, and the concentration of hydroxyapatite is 0.05-0.1 g / mL.

[0025] Preferably, in the first mixed solution, the concentration of DNA-like nanotubes is 1.875 μg / mL.

[0026] Preferably, in the first mixed solution, the concentration of hydroxyapatite is 0.075 g / mL.

[0027] In some embodiments of the present invention, the preparation method includes: injecting the first mixed solution into the porous titanium alloy after flow acid etching at 35-45°C, implanting it into the body, ultrasonicating, cooling, removing the outer pore part, and constructing an inner layer bone-promoting system.

[0028] In some embodiments of the present invention, the ultrasonic conditions are specifically: 240 W (power), 25-35 min.

[0029] In some embodiments of the present invention, the calcium salt is selected from one of calcium chloride, calcium sulfate and calcium nitrate, preferably calcium chloride.

[0030] In some embodiments of the present invention, the concentration of the calcium salt solution is 2-3 mol / L.

[0031] Preferably, the calcium salt is calcium chloride, and the concentration of the calcium chloride solution is 2-3 mol / L, more preferably 2.5 mol / L.

[0032] In some embodiments of the present invention, the porous titanium alloy implant is immersed in the calcium salt solution and allowed to stand for 15-30 min, preferably 15 min.

[0033] In some embodiments of the present invention, the concentration of sodium alginate is 0.01-0.03 g / mL, the concentration of gelatin is 0.1-0.3 g / mL, the solvent is PBS, and the solvent is PBS.

[0034] In some embodiments of the present invention, in the second mixed solution, the concentration of the DNA-like nanotubes is 35-45 μg / mL, and the concentration of the anti-tumor drug is 0.5-3 μg / mL.

[0035] Preferably, in the second mixed solution, the concentration of DNA-like nanotubes is 40 μg / mL.

[0036] Preferably, in the second mixed solution, the concentration of the anti-tumor drug is 2 μg / mL; further preferably, the anti-tumor drug is doxorubicin.

[0037] In some embodiments of the present invention, the porous titanium alloy implant is immersed in the second mixed solution and allowed to stand for 20-40 min, preferably 30 min, to construct an outer layer anti-tumor system.

[0038] The third aspect of the present invention provides the use of the porous titanium alloy implant double-layer sustained-release system described in the first aspect or the porous titanium alloy implant double-layer sustained-release system prepared by the preparation method described in the second aspect in the preparation of the following products;

[0039] The products include any one or more of the following:

[0040] I) Products that promote bone formation;

[0041] II) Anti-tumor products;

[0042] III) Products that extend the retention time of doxorubicin.

[0043] One or more of the above technical solutions have the following beneficial effects:

[0044] The present invention first loads osteogenic functional hydrogel in the inner layer of the porous titanium alloy implant, mimics the human bone collagen / HA structure, and hydroxyapatite has a regulatory effect on the osteogenic differentiation of mesenchymal stem cells. The DNA-like bionic nanotubes have the function of providing anchoring points for cells, mimicking the real physiological environment of human bones, and can regulate the differentiation of stem cells into osteoblasts. After the inner layer osteogenic system is loaded into the porous implant, the anti-tumor functional hydrogel is wrapped in the outer layer to promote the dissolution of hydrophobic doxorubicin drugs, so that they self-assemble into nano segments, increase the penetration of tumors, and the persistence of the effect.

[0045] The present invention prepares a modified porous titanium alloy implant, uses DNA-like bionic nanotubes to load drugs and mimics the human collagen / HA structure to achieve sustained release of anti-tumor drugs and promote the differentiation of mesenchymal stem cells into osteoblasts. The double-layer drug-loading system constructed by the present invention enables the release of anti-tumor and osteogenic drugs to have a temporal and spatial sequence, which can not only achieve efficient anti-tumor requirements, but also promote bone tissue repair and regeneration.

[0046] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0048] Figure 1Physical pictures of the porous titanium alloy implant used in Example 1 of the present invention, the porous titanium alloy implant with an inner layer osteogenic system, and the porous titanium alloy implant with an inner layer osteogenic system and an outer layer anti-tumor system (from left to right);

[0049] Figure 2 Potentiodynamic polarization diagrams of the porous titanium alloy implant after acid etching in Example 1 of the present invention, the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Example 1, and the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Example 2;

[0050] Figure 3 The surface contact angle statistics of the porous titanium alloy implant after acid etching in Example 1 of the present invention and the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Examples 1 and 3;

[0051] Figure 4 The biocompatibility test results of the porous titanium alloy implant after acid etching in Example 1 of the present invention, the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Example 3, and the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Example 1;

[0052] Figure 5 The effects of the acid-etched porous titanium alloy implant in Example 1 of the present invention, the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 3, and the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 1 on the mineralization level of mesenchymal stem cells;

[0053] Figure 6 The porous titanium alloy implant after acid etching in Example 1 of the present invention, the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 3 (and the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 1) on the expression of osteogenic-related genes in mesenchymal stem cells;

[0054] Figure 7 The anti-tumor effect test of the porous titanium alloy implant double-layer sustained-release system loaded with different doxorubicin concentrations prepared in Examples 1-3 of the present invention;

[0055] Figure 8 The release rate diagram of doxorubicin in the sustained-release system prepared in Example 1 of the present invention and Comparative Example 4 is shown. DETAILED DESCRIPTION

[0056] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0057] The porous titanium alloy implant used in the following examples is a TPMS structure with a pore size of 600-700 μm.

[0058] It should be noted that the DNA-like nanotubes used in the following examples are Janus-based nanotubes (JBNTs, self-assembled nanotubes inspired by DNA base pairs) with a diameter of 3.5 nm, which are obtained by self-assembly of compound 1 (monomer). The structure of compound 1 is as follows:

[0059]

[0060] Specifically, the Janus-based nanotubes were prepared by Zhou Libo et al. (Zhou L, Zhang W, Lee J, et al. Controlled Self-Assembly of DNA-Mimicking Nanotubes to Form a Layer-by-Layer Scaffold for Homeostatic Tissue Constructs. [J]. ACS applied materials&interfaces, 2021, 13(43): 51321-51332. DOI: 10.1021 / acsami.1c13345).

[0061] Example 1

[0062] A method for preparing a porous titanium alloy implant double-layer sustained-release system comprises the following steps:

[0063] (1) Flow acid etching of the 3D printed porous titanium alloy implant.

[0064] (2) Weigh 0.1 g of agarose powder, pour it into a 10 mL beaker, add 10 mL of PBS, heat and stir until dissolved, preheat at 40°C, mix the DNA-like nanotubes and hydroxyapatite, and add them to the agarose solution and mix them evenly to obtain the first mixed solution. In the first mixed solution, the concentration of DNA-like nanotubes is 1.875 μg / L, and the concentration of hydroxyapatite is 0.075 g / mL. Inject the 40°C mixed solution into the porous titanium alloy implant, ultrasonicate for 30 min, cool to room temperature, remove the part outside the pore, and construct the inner layer osteogenic system.

[0065] (4) Place the implant filled with agarose in a 2.5 mol / L calcium chloride solution for 15 min.

[0066] (5) Weigh 0.4 g of sodium alginate powder and 2 g of gelatin powder, pour into a 50 mL beaker, add 20 mL of PBS to dissolve, mix the DNA-like nanotubes with doxorubicin, and add them to the sodium alginate solution to mix evenly to obtain a second mixed solution. In the second mixed solution, the concentration of the DNA-like nanotubes is 40 μg / mL, and the concentration of doxorubicin is 2 μg / mL. Pour the mixed solution into a mold, place the porous part in (4) in it and let it stand for half an hour to construct the outer anti-tumor system.

[0067] Example 2

[0068] A method for preparing a porous titanium alloy implant double-layer sustained-release system is different from Example 1 in that the concentration of doxorubicin in the second mixed solution is 1.25 μg / mL, and the remaining steps are consistent with Example 1.

[0069] Example 3

[0070] A method for preparing a porous titanium alloy implant double-layer sustained-release system is different from Example 1 in that the concentration of doxorubicin in the second mixed solution is 0.63 μg / mL, and the remaining steps are consistent with Example 1.

[0071] Comparative Example 1

[0072] A method for preparing a porous titanium alloy implant single-layer sustained-release system comprises the following steps:

[0073] (1) Flow acid etching of the 3D printed porous titanium alloy implant.

[0074] (2) Weigh 0.1 g of agarose powder, pour it into a 10 mL beaker, add 10 mL of PBS, heat and stir until dissolved, preheat at 40°C, mix the DNA-like nanotubes and hydroxyapatite, and add them to the agarose solution and mix them evenly to obtain the first mixed solution. In the first mixed solution, the concentration of DNA-like nanotubes is 1.875 μg / mL, and the concentration of hydroxyapatite is 0.075 g / mL. Inject the 40°C mixed solution into the porous titanium alloy implant, ultrasonicate for 30 min, cool to room temperature, remove the part outside the pore, and construct the inner layer osteogenic system.

[0075] (4) The implant with the pores filled with agarose was placed in a 2.5 mol / L calcium chloride solution for 15 min to obtain a porous titanium alloy implant monolayer sustained-release system.

[0076] Comparative Example 2

[0077] A method for preparing a porous titanium alloy implant single-layer sustained-release system comprises the following steps:

[0078] (1) Flow acid etching of the 3D printed porous titanium alloy implant.

[0079] (2) Weigh 0.4 g of sodium alginate powder and 2 g of gelatin powder, pour into a 50 mL beaker, add 20 mL of PBS to dissolve, mix the DNA-like nanotubes with doxorubicin, and add them to the sodium alginate and gelatin solution and mix evenly to obtain a second mixed solution. In the second mixed solution, the concentration of DNA-like nanotubes is 40 μg / mL, and the concentration of doxorubicin is 2 μg / mL. Pour the mixed solution into a mold, place the acid-etched porous titanium alloy implant in it and let it stand for half an hour to construct the outer anti-tumor system and obtain a porous titanium alloy implant single-layer sustained-release system.

[0080] Comparative Example 3

[0081] A method for preparing a porous titanium alloy implant single-layer sustained-release system comprises the following steps:

[0082] (1) Flow acid etching of the 3D printed porous titanium alloy implant.

[0083] (2) Weigh 0.1 g of agarose powder, pour it into a 10 mL beaker, add 10 mL of PBS, heat and stir until dissolved, preheat at 40°C, mix the hydroxyapatite, and add it to the agarose solution and mix evenly to obtain the first mixed solution. In the first mixed solution, the concentration of DNA-like nanotubes is 1.875 μg / mL, and the concentration of hydroxyapatite is 0.075 g / mL. Inject the 40°C mixed solution into the porous titanium alloy implant, ultrasonicate for 30 min, cool to room temperature, remove the part outside the pore, and construct the inner layer osteogenic system.

[0084] (4) The implant with the pores filled with agarose was placed in a 2.5 mol / L calcium chloride solution for 15 min to obtain a porous titanium alloy implant monolayer sustained-release system.

[0085] Comparative Example 4

[0086] A method for preparing a porous titanium alloy implant single-layer sustained-release system comprises the following steps:

[0087] (1) Flow acid etching of the 3D printed porous titanium alloy implant.

[0088] (2) Weigh 0.4 g of sodium alginate powder and 2 g of gelatin powder, pour into a 50 mL beaker, add 20 mL of PBS to dissolve, mix doxorubicin and add to the sodium alginate and gelatin solution and mix evenly to obtain a second mixed solution. In the second mixed solution, the concentrations of doxorubicin were 2 μg / mL, 1.25 μg / mL and 0.63 μg / mL, respectively. Pour the mixed solution into a mold, place the acid-etched porous titanium alloy implant in it and let it stand for half an hour to construct the outer layer anti-tumor system and obtain a porous titanium alloy implant monolayer sustained-release system with different doxorubicin concentrations.

[0089] Performance Testing

[0090] 1. Characterization

[0091] Figure 1 From left to right in the middle are actual pictures of the porous titanium alloy implant used in Example 1 of the present invention, the porous titanium alloy implant constructed with an inner layer osteogenic system, and the porous titanium alloy implant constructed with an inner layer osteogenic system and an outer layer anti-tumor system. By constructing the inner layer osteogenic system and the outer layer anti-tumor system, the volume of the porous titanium alloy implant is gradually increased.

[0092] Figure 2 The potentiodynamic polarization diagrams of the porous titanium alloy implant (Ti) after acid etching in Example 1, the porous titanium alloy implant monolayer sustained release system (Ti+AG+HA / JBNTs) prepared in Comparative Example 1, and the porous titanium alloy implant monolayer sustained release system (Ti+Gel / SA+DOX / JBNTs) prepared in Comparative Example 2 are shown in Table 1. Figure 2 As shown, compared with the acid etching group (Ti), the corrosion potential of the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Examples 1 and 2 gradually increases, and the corrosion tendency decreases. In addition, the corrosion currents of these two groups are small, indicating that their corrosion efficiency is low and their corrosion resistance is high, indicating that the porous titanium alloy implant double-layer sustained-release system prepared in Example 1 has excellent corrosion resistance.

[0093] Figure 3 The surface contact angle statistics of the porous titanium alloy implant (Ti) after acid etching in Example 1 and the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Examples 1 and 3 are shown in FIG. Figure 3It can be seen that the surface contact angle of the acid-etched group is 91.473°, and the hydrophilicity is poor, close to hydrophobic. After loading the hydrogel containing hydroxyapatite (Ti-HA, i.e., the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 3), the surface contact angle is reduced to 26.133°, and the hydrophilicity is greatly improved. After adding JBNTs (Ti-HA+JBNTs, i.e., the porous titanium alloy implant monolayer sustained-release system prepared in Comparative Example 1), the hydrophilicity is further improved, and the contact angle is reduced to 19.587°. A surface with better hydrophilicity can provide a favorable environment for promoting cell adhesion and promote the adhesion of proteins.

[0094] Biocompatibility Rat mesenchymal stem cells (MSCs) were co-cultured with the acid-etched porous titanium alloy implant (Ti) in Example 1, the porous titanium alloy implant monolayer sustained-release system (Ti-HA) prepared in Comparative Example 3, and the porous titanium alloy implant monolayer sustained-release system (Ti-HA-JBNTs) prepared in Comparative Example 1 in a 24-well plate for 1, 4, and 7 days, and the cell viability was determined using a CCK-8 kit. The wavelength of the microplate reader used was 450 nm.

[0095] The experimental results are as follows Figure 4 As shown, through Figure 4 It can be seen that the porous titanium alloy implant single-layer sustained-release system prepared in Comparative Examples 1 and 3 has good biocompatibility, and has a good effect on promoting the proliferation of mesenchymal stem cells in the early stage. This example shows that the porous titanium alloy implant double-layer sustained-release system prepared in Example 1 has good biocompatibility, and has a good effect on promoting the proliferation of mesenchymal stem cells in the early stage.

[0096] Mineralized rat mesenchymal stem cells (MSCs) were co-cultured with the porous titanium alloy implant (Ti) after acid etching in Example 1, the porous titanium alloy implant monolayer sustained-release system (Ti-HA) prepared in Comparative Example 3, and the porous titanium alloy implant monolayer sustained-release system (Ti-HA+JBNTs) prepared in Comparative Example 1 in a 24-well plate for 21 days. The samples were detected using the Alizarin Red S staining method. The detection was performed using an ELISA reader at a wavelength of 405 nm.

[0097] The experimental results are as follows Figure 5 As shown, through Figure 5 It can be seen that after culturing mesenchymal stem cells for 21 days, the mineralization level of the hydroxyapatite-loaded group in Comparative Example 3 was improved, and the mineralization level was the highest after adding JBNTs. This example shows that the porous titanium alloy implant double-layer sustained-release system prepared in Example 1 has an excellent mineralization level for mesenchymal stem cells and can promote bone formation.

[0098] 4. Osteogenesis-related gene expression

[0099] Real-time polymerase chain reaction (RT-qPCR) was used to detect the expression of osteogenesis-related genes in cells. Rat mesenchymal stem cells (MSCs) were cultured in 24-well plates with the porous titanium alloy implant (Ti) after acid etching in Example 1, the porous titanium alloy implant monolayer sustained-release system (HA) prepared in Comparative Example 3, and the porous titanium alloy implant monolayer sustained-release system (HA+JBNTs) prepared in Comparative Example 1 for 7 days, and the expression levels of six genes in the cells were tested, namely alkaline phosphatase (ALP), bone morphogenetic protein (BMP), type I collagen (COL-1), osteocalcin (OCN), osteopontin (OPN) and Runt-related transcription factor (Runx2), and glyceraldehyde-3-phosphate dehydrogenase gene (GAPDH) was used as a reference gene to standardize the expression of the target gene. Total RNA in cells was extracted using TRIzol reagent (Invitrogen, USA), and RNA was reverse transcribed into cDNA using ReverTra Ace qPCR RT kit (TOYOBO, Japan). Finally, SYBR Green Realtime PCR MasterMix premix (TOYOBO, Japan) was used as the product dye, and the PCR reaction process was carried out on a fast real-time PCR reaction system (7900HT, Applied Biosystems, USA). The results were calculated using the relative quantitative comparison method (2-ΔΔCT). The primer sequences used are as follows:

[0100] BMP:

[0101] F:AACACAAGTCAGTGGGAGAGC (SEQ ID NO:1)

[0102] R:AACCCATGGTTGGTGTGTCC (SEQ ID NO:2)

[0103] COL-1:

[0104] F:GATGGACTCAACGGTCTCCC (SEQ ID NO:3)

[0105] R:CGGCCACCATCTTGAGACTT (SEQ ID NO:4)

[0106] Runx2:

[0107] F:ACGAATGCACTATCCAGCCA (SEQ ID NO:5)

[0108] R:GCAGGTACGTGTGGTAGTGA (SEQ ID NO:6)

[0109] ALP:

[0110] F:ACAACACCAACGCTCAGGTC (SEQ ID NO:7)

[0111] R:GTGACCTCGTTCCCCTGAGT (SEQ ID NO:8)

[0112] OCN:

[0113] F:ACTGCATTCTGCCTCTTGAC (SEQ ID NO:9)

[0114] R:GTAGCGCCGGAGTCTATTCA (SEQ ID NO:10)

[0115] OPN:

[0116] F:GAGACCATGCAGAGAGCGAG (SEQ ID NO:11)

[0117] R:TTGACCTCAGTCCGTAAGCC (SEQ ID NO:12)

[0118] GAPDH:

[0119] F:GGTGAAGGTCGGTGTGAACG (SEQ ID NO:13)

[0120] R:CTCGCTCCTGGAAGATGGTG (SEQ ID NO:14)

[0121] The experimental results are as follows Figure 6 As shown, through Figure 6 It can be seen that on the seventh day, the osteogenesis-related genes were measured, and it can be seen that the expression levels of the six genes in the titanium alloy implant loaded with hydroxyapatite were increased, and the expression levels of these genes were further increased after the addition of DNA-like nanotubes. This example shows that the porous titanium alloy implant double-layer sustained-release system prepared in Example 1 can promote the expression of osteogenesis-related genes in mesenchymal stem cells and promote bone formation.

[0122] 5. Anti-tumor

[0123] Osteosarcoma cells (HOS) were co-cultured in a 24-well plate for 48 hours with the porous titanium alloy implant double-layer sustained-release system containing different doxorubicin concentrations (0.63, 1.25, 2 μg / mL) prepared in Examples 1-3 and the porous titanium alloy implant single-layer sustained-release system containing different doxorubicin concentrations (0.63, 1.25, 2 μg / mL) prepared in Comparative Example 4, and cell viability was determined using a CCK-8 kit. The wavelength of the microplate reader used was 450 nm.

[0124] The experimental results are as follows Figure 7 As shown, through Figure 7 It can be seen that with the increase of doxorubicin concentration, the cell viability of osteosarcoma cells decreased, which was concentration-dependent. And under the condition of fixed doxorubicin concentration, the cell viability was further reduced after adding DNA-like nanotubes. This shows that DNA-like nanotubes can enhance the killing power of doxorubicin on osteosarcoma cells.

[0125] Sustained Release: The porous titanium alloy implant double-layer sustained-release system prepared in Example 1 and the porous titanium alloy implant single-layer sustained-release system with a doxorubicin concentration of 2 μg / mL prepared in Comparative Example 4 were placed in 3 mL of PBS, respectively, and incubated at 37°C. 2 mL of the solution was taken every day to detect the doxorubicin concentration using an ultraviolet spectrophotometer, and then 2 mL of fresh PBS was added.

[0126] Test results such as Figure 8 As shown, through Figure 8 It can be found that the group with the addition of JBNTs (i.e., the porous titanium alloy implant double-layer sustained-release system prepared in Example 1) has a longer drug release time and a slower initial release rate, which is in line with expectations. This shows that the porous titanium alloy implant double-layer sustained-release system provided by the present invention can reduce the release rate of doxorubicin and prolong the retention time of doxorubicin in the body.

[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous titanium alloy implant double-layer sustained-release system, characterized in that: The porous titanium alloy implant double-layer sustained-release system uses a porous titanium alloy as a skeleton, the interior of the porous titanium alloy is loaded with a first gel, and the exterior of the porous titanium alloy is coated with a second gel; The first gel contains DNA-like nanotubes and hydroxyapatite; The second gel contains DNA-like nanotubes loaded with anti-tumor drugs; The DNA-like nanotube is a Janus-based nanotube with a diameter of 3.5 nm, which is obtained by self-assembly of compound 1, and the structure of compound 1 is as follows: ; The anti-tumor drug includes doxorubicin; The first gel is agarose gel, and the second gel is sodium alginate and gelatin gel; A method for preparing a porous titanium alloy implant double-layer sustained-release system, comprising: The porous titanium alloy implant was subjected to flow acid etching; The DNA-like nanotubes and hydroxyapatite are mixed and added into an agarose solution to obtain a first mixed solution; injecting the first mixed solution into the porous titanium alloy implant after flow acid etching, and then immersing the porous titanium alloy implant in a calcium salt solution; The DNA-like nanotubes and the anti-tumor drug are mixed and added into a sodium alginate and gelatin solution to obtain a second mixed solution; The porous titanium alloy implant immersed in the calcium salt solution is taken out and placed in a second mixed solution, left to stand, and then taken out to obtain a porous titanium alloy implant double-layer sustained-release system; The calcium salt is selected from one of calcium chloride, calcium sulfate and calcium nitrate; the concentration of the calcium salt solution is 2-3 mol / L; In the sodium alginate and gelatin solution, the concentration of sodium alginate is 0.01-0.03 g / mL, the concentration of gelatin is 0.1-0.3 g / mL, and the solvent is PBS.

2. The porous titanium alloy implant double-layer sustained-release system according to claim 1, characterized in that: The concentration of the agarose solution is 0.01-0.02 g / mL, and the solvent is PBS; In the first mixed solution, the concentration of DNA-like nanotubes is 1.5-2 μg / mL, and the concentration of hydroxyapatite is 0.05-0.1 g / mL.

3. The porous titanium alloy implant double-layer sustained-release system according to claim 1, characterized in that: The preparation method comprises: injecting a first mixed solution into a porous titanium alloy after flow acid etching at 35-45° C., implanting the porous titanium alloy into the body, ultrasonicating, cooling, removing the outer pore part, and constructing an inner layer bone formation promoting system.

4. The porous titanium alloy implant double-layer sustained-release system according to claim 1, characterized in that: In the second mixed solution, the concentration of the DNA-like nanotubes is 35-45 μg / mL, and the concentration of the anti-tumor drug is 0.5-3 μg / mL; The anti-tumor drug is doxorubicin.

5. The porous titanium alloy implant double-layer sustained-release system according to claim 1, characterized in that: The porous titanium alloy implant is immersed in the second mixed solution and allowed to stand for 20-40 minutes to construct an outer layer anti-tumor system.

6. Use of the porous titanium alloy implant double-layer sustained-release system according to claim 1 in the preparation of the following products; in, The products include any one or more of the following: I) Products that promote bone formation; II) Anti-tumor products; III) Products that extend the retention time of doxorubicin.

Citation Information

Patent Citations

  • Gel-metal co-structure system and preparation method thereof

    CN114470334A